Faktor Pendorong Fear Of Missing Out (Fomo) dalam Keputusan Pembelian pada Saat Flash Sale Tanggal Kembar di E-Commerce Shopee - Alwi Shihab; Hani Hasanah; Laras Annisa Ulfitri Nedi (MANAJEMEN, 2025)
The development of digital technology has driven significant changes in consumer behavior, particularly through e-commerce platforms like Shopee. One effective marketing strategy for attracting consumers is the Flash Sale program on double-dates, which creates a sense of rush and urgency in making purchases. This phenomenon is closely related to the emergence of the Fear of Missing Out (FOMO), which is consumers' fear of missing out on an attractive offer or desired product. This study aims to determine the influence of FOMO and Flash Sale drivers on consumer purchasing decisions on Shopee. The approach used was quantitative, with a survey method using a questionnaire to 130 respondents who are active Shopee users in Tangerang City. Data were analyzed using the Partial Least Square (PLS) technique through SmartPLS 3.0 software, focusing on the influence of each variable on purchasing decisions. The results showed that both FOMO and Flash Sale have a positive and significant influence on purchasing decisions. This means that the stronger the fear of missing out felt by consumers, and the more attractive the Flash Sale promotion offered, the greater the likelihood of consumers making a purchase. These findings contribute to the development of more effective digital marketing strategies and provide insight into the dynamics of consumer behavior in the e-commerce era